Exploring the Drivers of Environmental Management Accounting and Environmental Performance: Empirical Evidence from Elbasan Region, Albania - Sulanjaku, Marsel; Ballkoci, Valbona (International Review of Management and Marketing, 2026)
The present study aims to explore the relationships of internal and external drivers influencing the adoption and implementation of environmental management accounting (EMA) in the manufacturing companies located in Elbasan, one of the major industrial zones of Albania. The research specifically investigates the effects of customer influence (CI), regulatory pressure (RP) and firm’s moral and social responsibility (MSR) on EMA. The research further, explores the impact of EMA on environmental performance (EP). This study tested the proposed hypotheses in the research model utilizing the data collected from 301 participants, accountants and senior officers employed in manufacturing companies located in Elbasan. Structural Equation Modeling (SEM) was utilized to assess the collected data and to examine the complex relationships between the constructs. The finding affirms that customer influence (CI), regulatory pressure (RP) and firm’s moral and social responsibility (MSR) have a significant and positive effect on environmental management accounting (EMA). Furthermore, the results confirm that EMA has a significant role in increasing the environmental performance (EP) of manufacturing companies located in Elbasan. This study provides significant empirical contribution in assessing the adoption of environmental management accounting (EMA) in an emerging economy such as Albania, where similar research remains limited.